Effect of long‐term clarithromycin therapy on prevention of pneumonia in older adults: A randomized, controlled trial. Issue 10 (15th August 2019) - Yamasue, Mari; Komiya, Kosaku; Yoshikawa, Hiroki; Kohno, Yoshihisa; Imamura, Yoshifumi; Otani, Satoshi; Shigenaga, Takehiko; Koga, Hironobu; Kishi, Kenji; Ichimiya, Tomoku; Tanaka, Hironori; Hara, Kanako; et al.
Abstract : Aim: Pneumonia in older adults is increasingly recognized as a healthcare issue in countries with an aging population. Long‐term macrolide therapy reduces exacerbations of chronic respiratory diseases, but its effects on the prevention of pneumonia have not been determined. Methods: We carried out a randomized, controlled trial to test the effect of long‐term clarithromycin therapy on the prevention of pneumonia among older adults. People aged ≥65 years who had recovered from pneumonia within the previous 3 months were recruited and randomly allocated to a long‐term, low‐dose clarithromycin (CAM) therapy group ( n = 13) or a control group ( n = 15). Results: Both groups were followed up until recurrence of pneumonia. The median follow‐up period was 251 days (95% CI 171–330) in the CAM group and 132 days (95% CI 67–196) in the control group ( P = 0.627). The recurrence rate of pneumonia was two out of 13 (15%) in the CAM group and five out of 15 (33%) in the control group ( P = 0.268). The median time to recurrence of pneumonia was 315 days (95% CI 249–382) in the CAM group and 260 days (95% CI 184–335) in the control group ( P = 0.260). None of the differences between groups were statistically significant. Conclusions: No statistically significant suppressive effects of long‐term, low‐dose macrolide therapy on the development of pneumonia among older people were found in this small sample. A large‐scale, randomized, controlled study is required.Geriatr Gerontol Int 2019; 19: 1006–1009 .